Boundary object as a trust buffer. The study of an open source code repository. - Ciesielska, Małgorzata; Petersen, Gregers (Tamara: Journal for Critical Organization Inquiry, 2013)
This paper discusses the impact of the Internet as communication technology and work environment on changing professional relations and work practices. In particular the paper contributes to a better understanding of collaboration processes enabled by the web and hereby draw a field for further research on trust within Open Source Software (OSS) communities. Having two contradictory interpretations of the technical structure of the project development we indicate its ambiguity to make a point about the meaning of trust and distrust in crating the space for cooperation. Neither trust is necessary nor distrust destructive thanks to the boundary object - the source code repository - that serves as a sole meeting point between OSS community and the company.